Diagnostic diversities of Clear Fluid encountered during Fine needle aspiration cytology with an analysis of various variables. (Bangladesh Journal of Medical Science, 2019)
Background: Incidental finding of clear fluid during fine needle aspiration (FNA) is not rare in day to day practice of cytology. Though clear in appearance, cells obtained from it may yield a diverse diagnosis ranging from an inconclusive opinion to a malignant lesion. So, clear fluid is not non-significant always; lack of proper processing and examination may prove fatal to a patient.Aim: To evaluate the diverse diagnosis of clear fluid.Materials and methods: During a period of three years, hundred and seven cases which yielded clear fluid during FNAC from different parts of the body were studied. Direct and indirect smears (wherever applicable) was prepared, stained and examined microscopically.Results: Of these 107 cases of clear fluid, Male: Female ratio was 1: 1.6. Maximum cases - 55 (51.40%) was found in the age group 21 to 40 years. Trunk held the most number of lesions - 54 cases (50.46%). FNA results were interpreted as inconclusive in 19 cases (17.76%), benign in 84 cases (78.50%), suspicious in 01 case (0.93%) and malignant in 03 cases (2.80%). Epidermal cyst was the most common benign lesion - 16 cases (14.95%). Malignant lesions found were papillary carcinoma of thyroid, carcinoma of breast and metastatic squamous cell carcinoma – one case each.Conclusion: Our study emphasizes on the importance of proper examination of clear fluid as it may prove helpful in an undiagnosed case of malignancy and it may also improvise the learning of young pathologists.Bangladesh Journal of Medical Science Vol.18(4) 2019 p.753-755